CXCR2 Small-Molecule Antagonist Combats Chemoresistance and Enhances Immunotherapy in Triple-Negative Breast Cancer - Ghallab, Alaa M.; Eissa, Reda A.; El Tayebi, Hend M. (Frontiers in Pharmacology, 2022)
Triple negative breast cancer (TNBC) is the most malignant subtype of breast cancer as the absence of cell surface receptors renders it more difficult to be therapeutically targeted. Chemokine receptor 2 (CXCR2) has been suggested not only to promote therapy resistance and suppress immunotherapy but it is also known to possess a positive cross talk with the multifunctional cytokine transforming growth factor beta (TGF‐β). Here we showed that CXCR2 and TGF‐ β signaling were both upregulated in human TNBC biopsies. CXCR2 inhibition abrogated Doxorubicin‐mediated TGF‐ β upregulation in 3D ex vivo TNBC culture and eliminated the drug resistance in TNBC mammospheres, suggesting a vital role for CXCR2 in TNBC Doxorubicin-resistance via TGFβ signaling regulation. Moreover, CXCR2 inhibition improved the efficacy of the immunotherapeutic drug "Atezolizumab" where the combined inhibition of CXCR2 and PDL-1 in TNBC ex vivo culture showed an additive effect in cytotoxicity. Altogether, the current study suggests CXCR2 inhibitors as a promising approach to improve TNBC treatment if used in combination with chemotherapy and/or immunotherapy.